Уул уурхайн компаниудийн нийгмийн хариуцлагын чиглэлээр гаргасан хууль эрх зүйн актууд, тэдгээрийн хэрэгжилтэнд хийсэн шинжилгээ - С.Бурмаа, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
This article dealt with issues on social responsibility within the mining laws and legalization documentations. It also concluded the implementation and monitoring of mining companies’ social responsibility reports and current situations in conjunction with their practical functions.